2001
DOI: 10.1002/chin.200102157
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Synthesis and Analysis of Structural Features of Phenoxazine Analogues Needed to Reverse Vinblastine Resistance in Multidrug Resistant (MDR) Cancer Cells.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Phenothiazines 1a and 1b , phenoxazines 3a – 3d , 1-phenylpiperazines, 5 H -dibenzo­[ b , f ]­azepine 9 , 10,11-dihydro-5 H -dibenz­[ b , f ]­azepine 10 , acridone 11 (Scheme ), diphenylamine 12 , 2-phenoxyaniline 13 , anilines, and benzylamine precursors for 22a – 22b were purchased or synthesized according to literature methods. The starting 2-chloro-10 H -phenoxazine 3b and 2,8-dichloro-10 H -phenoxazine 3c were prepared in five steps starting via a 2-amino-2′-chlorodiaryl ether according to literature procedures . The 10 H -phenoxazine-3-carbonitrile 3d was prepared as described by Eastmond et al In general, synthesis of various intermediate carbamoyl chlorides 14 was accomplished without isolating them by chlorocarbonylation of N -heterocycles or secondary amines with bis­(trichloromethyl) carbonate in 1,2-dichloroethane and pyridine, as illustrated in Scheme .…”
Section: Chemistrymentioning
confidence: 99%
“…Phenothiazines 1a and 1b , phenoxazines 3a – 3d , 1-phenylpiperazines, 5 H -dibenzo­[ b , f ]­azepine 9 , 10,11-dihydro-5 H -dibenz­[ b , f ]­azepine 10 , acridone 11 (Scheme ), diphenylamine 12 , 2-phenoxyaniline 13 , anilines, and benzylamine precursors for 22a – 22b were purchased or synthesized according to literature methods. The starting 2-chloro-10 H -phenoxazine 3b and 2,8-dichloro-10 H -phenoxazine 3c were prepared in five steps starting via a 2-amino-2′-chlorodiaryl ether according to literature procedures . The 10 H -phenoxazine-3-carbonitrile 3d was prepared as described by Eastmond et al In general, synthesis of various intermediate carbamoyl chlorides 14 was accomplished without isolating them by chlorocarbonylation of N -heterocycles or secondary amines with bis­(trichloromethyl) carbonate in 1,2-dichloroethane and pyridine, as illustrated in Scheme .…”
Section: Chemistrymentioning
confidence: 99%
“…Earlier studies on the secondary metabolites produced by C. gambosa, demonstrated that in culture, this fungal species synthesized an orange crystalline metabolite which was shown to be the phenoxazine derivatives (phenoxazone and a-amino-phenoxazone) (Clemencon, 1987;Moncalvo et al, 1991;Schlunegger et al, 1976). These derivatives are used extensively in medicine, biology and chemistry (Eregowda et al, 2000;Kalpana et al, 1999;Shimizu et al, 2004;Sridhar et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Actinomycin D ( 13 ), bearing a phenoxazine chromophore, represents one of the older chemotherapy drugs and is primarily used as an investigative tool in cell biology to inhibit transcription . Meanwhile, the anticancer activities of several phenoxazinones on human leukemia cell lines have also been investigated. In addition, N -substituted phenoxazines have recently been identified as modulators of MDR , and as potent specific inhibitors of Akt signaling …”
Section: Introductionmentioning
confidence: 99%